Isoglitter - Bucknum, Michael J. (2012)
A novel orthorhombic lattice is described that is generated upon a 1,4-cyclohexadieneoid motif, and is a model of a potential allotrope of C. The orthorhombic lattice (Ammm, space group #65) that is described, is called isoglitter as it is a structural relative of the tetragonal glitter lattice (P4₂/mmc, space group #131) first proposed in 1994 by Bucknum et al. A geometrical optimization of the isoglitter lattice, employing the Cambridge Serial Total Energy Package (CASTEP) algorithm based upon density functional theory (DFT) was performed. The present report is an account of the CASTEP optimized isoglitter crystal structure, including an idealized drawing of the unit cell, and a set of optimized crystallographic coordinates for isoglitter. Results of an electronic band structure calculation, together with a density of states (DOS) profile for the lattice based upon CASTEP, are reported as well. The unit cell of isoglitter contains 8 C atoms and has a DFT modeled density of about 3.009 g/cm³. Isoglitter is comprised entirely of planar and chair-like 6-gons, and puckered 8-gons, in its structural pattern. The Wells point symbol for the network is cited here as (6³)(6⁵.8) and it is thus not a true graphene–diamond hybrid, where this point symbol translates to a Schlaefli symbol given as (62/9, 31/2). Based upon its connectivity, comprised of 3-connected trigonal planar vertices in a 1-to-1 stoichiometry with 4-connected tetrahedral vertices, the novel lattice is positioned midway between the graphene sheet, located at (6, 3), and the diamond lattice, located at (6, 4), in the topology mapping of structures described earlier by Wells.